SECURITY BRANDING SEBAGAI SALAH SATU STRATEGI START-UP INDONESIA UNTUK BERTAHAN DALAM MASA PANDEMIK COVID-19 - Michelle Jasmine H.; Livia Angelica; Jovani Liman; Samantha Teonata; Desi Anggita Septhesia; Jason Pangkey; Quena Fatin P. P. (Jurnal Vicidi, 2020)
The writing of this paper aims to answer the question, "How can start-ups use social media to build security branding as a strategy for start-up businesses to survive in a pandemic?" The background of this writing is the condition of the world which is currently in the period of the COVID-19 pandemic. This research was carried out using the Literature Study method on the definition of security branding, Indonesian start-ups, pandemics, and the various impacts caused by an epidemic on brands. The author also includes several case studies of a pandemic that has an impact on brands, as well as another case study on how security branding has been implemented in the case of creating a sense of security for consumers. These journals are taken from various sources. Through this research, the authors found that in dealing with the COVID-19 pandemic, businesses can use security branding so that people can trust the security of a brand, and this has an impact on reducing the economic impact caused by the outbreak. Keywords: security branding, pandemic.